Hubungan Stres Akademik dengan Student Engagement Pondok Pesantren di Kota Bandung - Ima Nurul Azmi; Dewi Rosiana (UNISBA Press, 2024)
Abstract. Islamic boarding schools are schools with distinctive characteristics that differ from regular public schools, starting from the school system to school rules. The stress experienced by students (santri) in Islamic boarding schools is caused by various academic demands in the boarding school, as students must adhere to various rules, activities, and study hours from morning until night. The academic demands and the workload of activities experienced by students in Islamic boarding schools can lead to a lack of focus during learning, disrupting student engagement and causing students to become tired, easily bored, and inactive during lessons. Therefore, this research is conducted with the aim of determining the relationship between academic stress variables and student engagement in Islamic boarding schools in the city of Bandung. The hypothesis proposed in this study is that there is a negative relationship between academic stress and student engagement in Islamic boarding schools in Bandung. The respondents consist of 273 male and female students aged 12-15 years, from grade 7 to grade 9. The research method used is correlational method using Spearman Rank correlation test. The results of this study indicate a significant relationship between academic stress and student engagement in Islamic boarding schools in Bandung with a correlation coefficient of -0.153. Abstrak. Pondok pesantren merupakan sekolah dengan ciri khas yang berbeda dengan sekola umum biasa mulai dari sistem sekolah hingga aturan sekolah. Stres yang telah dialami oleh santri di pondok pesantren disebabkan karena berbagai tuntutan akademik di pondok pesantren karena santri harus mengikuti berbagai aturan, kegiatan, serta jam belajar mulai dari pagi hingga malam. Tuntutan akademik dan juga beban kegiatan yang dialami santri di pondok pesantren dapat menyebabkan santri menjadi kurang fokus selama pembelajaran, sehingga student engagement menjadi terganggu yang membuat santri menjadi lelah, mudah bosan serta tidak aktif selama pembelajaran. Tujuan penelitian ini untuk mengetahui hubungan antara variabel stres akademik dengan student engagement pondok pesantren di Kota Bandung. Hipotesis yang diajukan pada penelitian ini ialah terdapat hubungan negatif antara stres akademik dengan student engagement pondok pesantren di Kota Bandung. Jumlah responden sebanyak 273 santri laki-laki dan perempuan yang berusia 12-15 tahun, kelas 7 hingga kelas 9. Analisis penelitian ini menggunakan uji korelasional spearman’s rho. Hasil penelitian ini menyatakan bahwa terdapat hubungan signifikan antara stres akademik dengan student engagement pondok pesantren di Kota Bandung dengan koefisien korelasi -0,153.